Noninvasive 2D and 3D Mapping of Root Zone Soil Moisture Through the Detection of Coarse Roots With Ground‐Penetrating Radar. Issue 5 (9th May 2020) - Liu, X.; Chen, J.; Butnor, J. R.; Qin, G.; Cui, X.; Fan, B.; Lin, H.; Guo, L.
Abstract: Root zone soil moisture (RZSM) is important in sustaining terrestrial ecosystems and water cycling. However, noninvasive mapping of RZSM remains challenging in the field, especially its spatial variability at local scales. We propose a novel method of applying ground‐penetrating radar (GPR) for noninvasive determination of RZSM. First, this method identified coarse root reflections in GPR images to obtain the reflected wave velocity and soil water storage at various locations. Then, the horizontal distributions of soil water storage to different depths were reconstructed using the inverse distance weighted interpolation. The difference in soil water storage between two depths was converted into 2D RZSM distribution for a specific depth interval. Finally, 2D RZSM distributions from a range of depths were combined to produce a 3D visualization of RZSM. The proposed method was validated in two field plots (30 m by 30 m) in shrublands. The comparisons with 2D RZSM distributions from soil cores sampled at 0.2‐m depth intervals suggested a reasonable correspondence in both spatial patterns and absolute values, with the average root‐mean‐square error less than 0.017 m 3 ·m −3 and correlation coefficients ranging from 0.502 to 0.798 in both plots. Furthermore, 3D visualizations of RZSM were generated based on GPR estimates to demonstrate the spatial variability of soil moisture at the study scale. The proposed method enhances noninvasive characterization of soil moisture down to the root zone, which contributes to a better understanding of the local‐scale variability of soil moisture in the subsoil as well as the ecohydrological processes in the soil‐plant‐atmosphere continuum. Key Points: We propose a novel method of mapping root zone soil moisture noninvasively by ground‐penetrating radar This method reconstructs 2D/3D distributions of soil moisture by combining the identification of root's signals and spatial interpolation Soil moisture distributions noninvasively mapped by the proposed method matched reasonably those obtained by augering